2009
DOI: 10.1017/s0960428609005393
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Classification of the Marchantiophyta

Abstract: Input from molecular phylogenetics in the past five years has substantially altered concepts of systematic relationships among liverworts. While these studies have confirmed the monophyly of phylum Marchantiophyta, they have demonstrated that many previously recognised ranks within the hierarchy are unnatural and in need of modification. Changes in the ranks of suborder and above have been proposed by various workers, but modifications in the circumscription of genera and families are still required. A compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
234
2
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(257 citation statements)
references
References 51 publications
11
234
2
10
Order By: Relevance
“…This author also suggests that the more specialized the taxonomic group (e.g., Marchantiales, complex thalloid liverworts) the more frequently these structures are not found. On the contrary, molecular methods has been useful to unraveling the liverwort phylogeny, hence Jungermanniales (leafy liverworts) are nowadays considered a more derived group (Crandall-Stottler et al 2009), in which oilbodies are commonly found. Otherwise, considering that the levels of UV radiation in past geological eras was higher than present levels, it is possible that these structures play a protective role against this type of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…This author also suggests that the more specialized the taxonomic group (e.g., Marchantiales, complex thalloid liverworts) the more frequently these structures are not found. On the contrary, molecular methods has been useful to unraveling the liverwort phylogeny, hence Jungermanniales (leafy liverworts) are nowadays considered a more derived group (Crandall-Stottler et al 2009), in which oilbodies are commonly found. Otherwise, considering that the levels of UV radiation in past geological eras was higher than present levels, it is possible that these structures play a protective role against this type of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent progress in liverwort phylogeny is reflected in the new liverwort classification of Crandall-Stotler et al (2009). However, several genera have not yet been sequenced or been tested for their monophyly.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular phylogenetic studies have substantiated the position of liverworts (Marchantiophyta) as the earliest diverging extant main lineage of land plants (Qiu et al 2006) and provided numerous new insights into their classification (Crandall-Stotler et al 2009). The leafy liverworts represent a derived lineage that basically splits into two main clades assigned to as Jungermanniales and Porellales (Heinrichs et al 2005He-Nygrén et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[37] The above results indicate that EO components can be utilized for chemosystematic studies of liverworts. These studies suggest that the liverworts belonging to the order Metzgeriales (simple thalloid) and Marchantiales (complex thalloid) can be distinguished from the leafy liverworts (order Jungermanniales) by the presence of β-barbatene (8) and anastreptene (7). Analysis of EO constituents showed that longipinane-, longifolane-and longibornanetype sesquiterpenoids are characteristic components found in Scapania undulata, cadinanes for Conocephalum conicum, bazzananes for the genus Bazzania and eudesmanolides in the genus Diplophyllum.…”
Section: Early Studies On the Essential Oils From Liverwort Speciesmentioning
confidence: 95%
“…[5,6] Liverworts (Marchantiophyta) are a relatively small group of plants with an estimated 5000-6000 species in the world. [7] Three morphological types of plant bodies have generally been recognized and used in liverwort classification. These are 'complex thalloid' including~6% of extant species diversity, 'simple thalloid' (~8%) and 'leafy' liverworts (~86%).…”
Section: Introductionmentioning
confidence: 99%